The Y Combinator is a classic lambda calculus construct that many people find baffling. Here's my attempt to explain it as clearly as possible (no promises!). Familiarity with Haskell syntax is assumed.
The problem we're trying to solve is how to write an anonymous function (a "lambda") that is recursive. Normally, if you want to write a recursive function, it looks like this:
fac n = if n == 0 then 1
else n * fac (n-1)
Note that fac
appears in the function body. Therein lies the problem: if fac
were a lambda, what name would you use to refer to it?
This may seem like a non-issue; why not just write the recursive function normally? Why use a lambda? Well, in the lambda calculus, there are no "normal functions," there are only lambdas. So the Y Combinator was invented as a means of writing recursive functions in pure lambda calculus.
Getting back to the problem: we need to rewrite fac
so that it doesn't reference itself in its own function body. Here's the trick that forms the basis of the Y Combinator: fac
can't refer to fac
, but it can refer to a generic function supplied as an argument. In other words, we rewrite fac
to take an extra argument, f
, which is a function. Then, instead of fac
recursively calling fac
, it will just call f
. It looks like this:
fac f n = if n == 0 then 1
else n * f (n-1)
Now when we call fac
, we'll call it as fac fac 5
, so that when fac
calls f
, it'll really be calling itself. Recursion!
There's an error in the above code snippet though. Since f
is fac
, it needs to take another argument:
fac f n = if n == 0 then 1
else n * f f (n-1)
Excellent. With all the references removed, we're now able to write fac
as a lambda:
fac = \f n ->
if n == 0 then 1
else n * f f (n-1)
Note that fac
itself takes no arguments. This is known as the "fixed-point" version of fac
, also known as "points-free" style (or "pointless" by its detractors).
There's just one more problem. Recall that we are now calling fac fac
instead of just fac
. That won't do! Think of how we would map our fac
lambda to a list:
-- won't work! our lambda takes too many arguments!
map (\f n -> if n == 0 then 1 else n * f f (n-1)) [1..10]
To fix this, we need to supply the first argument to our lambda, f
. Recall that this is the lambda itself, so now we have:
fac = (\f n -> if n == 0 then 1 else n * f f (n-1))
(\f n -> if n == 0 then 1 else n * f f (n-1))
-- our mapped lambda now looks like this
map ((\f n -> if n == 0 then 1 else n * f f (n-1))
(\f n -> if n == 0 then 1 else n * f f (n-1))) [1..10]
This will actually work! (Okay, not quite; see Addendum.) But it goes without saying that this is rather ugly; any time we want to write a recursive lambda, we have to write it out twice! Plus, wherever we recurse, we have to call f f
instead of just f
. This is where the Y Combinator comes in: it abstracts away these annoyances.
We'll start by rewriting fac
like so:
fac f = (\ff n -> if n == 0 then 1 else n * ff (n-1))
(f f)
-- or as a lambda:
fac = \f -> (\ff n -> if n == 0 then 1 else n * ff (n-1))
(f f)
Do you see what's different here? Instead of calling f f
inside the factorial logic, we pass it in as an argument; ff = (f f)
.
What is the purpose of this? You'll see in just a second. First, we're going to rewrite our doubly-applied version with this new style:
fac = (\f -> (\ff n -> if n == 0 then 1 else n * ff (n-1)) (f f))
(\f -> (\ff n -> if n == 0 then 1 else n * ff (n-1)) (f f))
Now we can pull out the factorial logic:
-- looks just like our first lambda, but without the double f
fac' = \f n ->
if n == 0 then 1
else n * f (n-1)
fac = (\f -> fac' (f f))
(\f -> fac' (f f))
Note that we couldn't do this before because of the double f
.
Look at how general our fac
function is! In fact, if we replace fac'
with a generic function, we get:
-- the Y Combinator!
y fn = (\f -> fn (f f))
(\f -> fn (f f))
-- as a lambda:
y = \fn -> (\f -> fn (f f))
(\f -> fn (f f))
If you're brave, you can now write fac 5
as it would appear in pure lambda calculus:
-- Y Combinator
(\fn -> (\f -> fn (f f))
(\f -> fn (f f)))
-- applied to fac
(\f n -> if n == 0 then 1
else n * f (n-1))
-- applied to 5
5
Just to make sure this works, we can try it with a Fibonnaci function as well:
-- standard Fibonnaci implementation
fib n = if n == 0 then 0
else if n == 1 then 1
else fib (n-1) + fib (n-2))
-- version that takes itself as an argument
fib' f n = if n == 0 then 0
else if n == 1 then 1
else f f (n-1) + f f (n-2))
-- Y Combinator
(\fn -> (\f -> fn (f f))
(\f -> fn (f f)))
-- applied to fib'
(\f n -> if n == 0 then 0
else if n == 1 then 1
else f (n-1) + f (n-2))
-- applied to 5
5
These examples should return 120 and 5, respectively.
Haskell actually won't allow you to write f f
, because it's strictly typed. To get around this, import Unsafe.Coerce
and preface every occurance of f f
with unsafeCoerce f f
.
However, Haskell also has a much simpler way of writing a fixed-point combinator (of which the Y Combinator is only one example):
fix f = f (fix f)
This is possible because Haskell is "lazily evaluated," which means it only evaluates expressions when their value is needed. Otherwise, when it tried to evaluate the definition of fix
, it would recurse forever and hang.
You can verify for yourself that fix
works with the previous examples, no unsafeCoerce
necessary. But why does it work? Let's expand it a bit:
fac' = \f n ->
if n == 0 then 1
else n * f (n-1)
-- fac is just the repeated application of fac' to itself
fac = fix fac'
= fac' (fix fac')
= fac' (fac' (fix fac'))
= fac' (fac' (fac' (...)))
-- full expansion of fac 2:
-- first iteration (n == 2)
(\f n -> if n == 0 then 1 else n * f (n-1))
-- applied to second iteration (n == 1)
(\f n -> if n == 0 then 1 else n * f (n-1))
-- applied to second iteration (n == 0)
(\f n -> if n == 0 then 1 else n * f (n-1))
-- ...applied to infinitely more iterations...
(fix fac')
-- applied to 2
2
-- since we know the value of n, let's reduce the ifs:
(\f n -> n * f (n-1)) -- n == 2
(\f n -> n * f (n-1)) -- n == 1
(1) -- n == 0
2
What happened to the "infinitely more iterations?" Well, in the n == 0
case, f
isn't used, so Haskell doesn't try to evaluate it! Pretty cool, huh? Let's finish up the reduction:
-- reduce the n == 1 case
-- note the disappearance of the f argument
(\f n -> n * f (n-1)) -- n == 2
(\n -> n * (1)) -- n == 1
2
-- reduce the n == 2 case
(\n -> n * (\n -> n * (1)) (n-1)) -- n == 2
2
-- further reduction
(\n -> n * (n-1) * (1))
2
-- and finally
2 * (2-1) * (1) = 2